SCIENTIFIC AND ECONOMIC ANALYSIS OF INDUSTRIAL ENTERPRISES PURCHASING TEXTILE OILS IN UZBEKISTAN (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article presents a scientific and economic assessment of the market for textile oils and specialty lubricants used by industrial textile enterprises in Uzbekistan. The study does not examine domestic production of textile oils; instead, it focuses on purchasing enterprises, imported product classes, technical quality requirements, price differences and the effect of lubricant procurement decisions on enterprise-level economics. Open Volza import analytics for the Uzbekistan textile lubricant and HSN Code 2710 segment indicate 78 buyers, 109 global suppliers and 286 import shipments, with POSCO International Textile, Biryuza Group and Texparts UZ appearing among the most active buyers [1]. From a technical perspective, the central demand is associated with ISO VG 32 needle/sinker oils, washable needle and sinker lubricants, elastane compatibility, anticorrosion behavior and non-staining performance on fabrics. Open price benchmarks vary from 5.85 to 24.41 EUR/L, showing that package size, brand positioning and product class can substantially change annual procurement budgets and price sensitivity. The results indicate that although textile oils usually represent a small share of total manufacturing cost, they are strategic process inputs because downtime, accelerated needle and sinker wear, repeated washing, oil stains and export-quality risks can generate significant indirect losses. The article proposes a total-cost-of-ownership approach for procurement decisions in textile enterprises.